Schwarz boundary-value problems for solutions of a generalized Cauchy-Riemann system with a singular line - Plaksa, S.A. (Український математичний вісник, 2019)
We consider a generalized Cauchy–Riemann system with a rectilinear singular interval of the real axis. Schwarz boundary value problems for generalized analytic functions which satisfy the mentioned system are reduced to the Fredholm integral equations of the second kind under natural assumptions relating to the boundary of a domain and the given boundary functions.